2006
DOI: 10.1590/s0102-86502006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enoxaparin on the healing of abdominal wall in rats: study on breaking strength and histopatology

Abstract: Purpose:To evaluate the influence of enoxaparin on the abdominal wall healing. Methods: Sixty Wistar male rats were randomly distributed into two experimental groups. Group E: consisted of 30 rats, submitted to abdominal suture and treated with enoxaparin in a dose of 1 mg/kg of body weight, subcutaneously administered from immediate postoperative until the 7 th day; Group C: consisted of 30 rats submitted to abdominal suture and treated with the equivalent dose per volume of NaCl 0.9%. The animals were submit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…the use of enoxaparin caused an increase on the tensile breaking strength and worse collagen disposition at the 7 th postoperative day 15 . Experimental group was included significant loss of tensile strength in our study.…”
Section: Discussionmentioning
confidence: 97%
“…the use of enoxaparin caused an increase on the tensile breaking strength and worse collagen disposition at the 7 th postoperative day 15 . Experimental group was included significant loss of tensile strength in our study.…”
Section: Discussionmentioning
confidence: 97%
“…The losses may have been associated with surgical stress 14 . Weight loss has been described in previous studies on wound healing 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The suture dehiscences both of intestinal anastomosis and of surgical wound complications are involved in the genesis of infections and increased mortality and morbidity rates, hospital permanence and high costs; therefore, factors that inhibit the inflammatory mediators may have undesirable effects on the process of repairing and healing of wounds 17,18,20 . Studies have reported that some drugs with antiinflammatory or pro-inflammatory action, including diclofenac sodium 8,13 , misoprostol 17 , alter the wound healing, interfering with inflammation and collagen deposition.…”
Section: Discussionmentioning
confidence: 99%